2010
DOI: 10.1016/j.jasms.2009.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and dynamics of biopharmaceuticals: Transition of mass spectrometry-based tools from academe to industry

Abstract: Mass spectrometry plays a very visible role in biopharmaceutical industry, although its use in development, characterization, and quality control of protein drugs is mostly limited to the analysis of covalent structure (amino acid sequence and post-translational modifications). Despite the centrality of protein conformation to biological activity, stability, and safety of biopharmaceutical products, the expanding arsenal of mass spectrometry-based methods that are currently available to probe higher order stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 77 publications
1
59
0
3
Order By: Relevance
“…It is now and will continue to be a very dynamic area of research, which will certainly continue to advance the fields of biophysics and structural biology. Importantly, studies using MS-based methods of protein characterization beyond covalent structure analysis are no longer confined to the academic labs, but have become accepted tools in biotechnology and biopharmaceutical industry, 51,82,83 where their role will also undoubtedly continue to expand.…”
Section: Discussionmentioning
confidence: 99%
“…It is now and will continue to be a very dynamic area of research, which will certainly continue to advance the fields of biophysics and structural biology. Importantly, studies using MS-based methods of protein characterization beyond covalent structure analysis are no longer confined to the academic labs, but have become accepted tools in biotechnology and biopharmaceutical industry, 51,82,83 where their role will also undoubtedly continue to expand.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have shown that the misassignment of charges using this approach is common in heterogeneous systems, 21 such as extensively glycosylated proteins, due to the dependence of the ionic charge on the physical size of biopolymers. 27,28 Glycoforms with higher carbohydrate content have larger surface area and, therefore, will accumulate more charges upon transition from solution to the gas phase during the ESI process. As a result, they will be overrepresented at the lower m/z end of the charge state distribution envelope, while the glycoforms with lower carbohydrate content will be overrepresented at the opposite end of the envelope.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The labeled protein is HDX-MS is particularly well suited for assessing domain specific comparability between proteins and protein therapeutics. 48,77 There are several examples in the literature describing the application of HDX-MS to understanding conformational changes brought on by aggregation of proteins and mAbs. 55,78 The impact of PTMs and chemical modifications has also been studied and it has been found that Fc domain glycosylation structure and Fc domain oxidation can have impacts on the exchange kinetics of discrete, structurally distinct regions of the Fc.…”
Section: ■ Hydrogen/deuterium Exchange Mass Spectrometry (Hdx-ms) Of mentioning
confidence: 99%